Brave - Chmakova, Svetlana, 1979- (Yen Press, 2017)
Althouh shy Jensen daydreams about being a hero, the reality of his school life is very different, but when two school newspapers writers begin to put him in their stories, he discovers he may have to find real solutions for his problems.